Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1002/alz.13007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a ketogenic and low‐fat diet on the human metabolome, microbiome, and foodome in adults at risk for Alzheimer's disease

Abstract: INTRODUCTIONThe ketogenic diet (KD) is an intriguing therapeutic candidate for Alzheimer's disease (AD) given its protective effects against metabolic dysregulation and seizures. Gut microbiota are essential for KD‐mediated neuroprotection against seizures as well as modulation of bile acids, which play a major role in cholesterol metabolism. These relationships motivated our analysis of gut microbiota and metabolites related to cognitive status following a controlled KD intervention compared with a low‐fat‐di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The development of Alzheimer’s disease [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer’s disease have been investigated [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Numerous studies are also available regarding treatments with probiotics […”
Section: Discussionmentioning
confidence: 99%
“…The development of Alzheimer’s disease [ 69 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 ] and the mechanisms through which the microbiome can contribute to the progression of Alzheimer’s disease have been investigated [ 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 ]. Numerous studies are also available regarding treatments with probiotics […”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] A low‐fat diet or a modified Mediterranean ketogenic diet for 6 weeks can benefit adults with mild cognitive impairment. [ 16 ] González‐Domínguez et al revealed that the level of Trp from AD and mild cognitive impairment patients was decreased. [ 17 ] Numerous studies revealed that Trp and its bacterial metabolites indoles were closely related to cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…We excluded patients receiving antibiotic, prebiotic, and probiotic therapy since such treatments may alter the microbiota and might affect systemic inflammation and the biomarkers of the intestinal barrier [ 37 ]. Additionally, patients on a ketogenic diet were excluded due to the high fat intake and production of ketone bodies in the liver [ 38 ]. Several studies have shown that a high fat diet alters gut microbiota and intestinal permeability [ 39 , 40 ].…”
Section: Methodsmentioning
confidence: 99%